PERIODIC MEDICAL CHECKUP AMONG HEALTH WORKERS: A DESCRIPTIVE CROSS-SECTIONAL SURVEY AT A TEACHING HOSPITAL IN GHANA - Surazu, B.; Muktar, A.; Salifu, A. (UDS International Journal of Development, 2023)
This study aimed at assessing the prevalence of periodic medical checkup by health professionals at the Tamale Teaching Hospital. This was a cross-sectional study with a quantitative research approach. Three hundred (300) health care personnel, including nurses, doctors and medical laboratory scientists were selected using a convenience sampling method. Data was collected using self-administered questionnaire, with questions classified under demographics, knowledge, perception and practice. Data processing was carried out using Microsoft Excel. Data was checked, cleaned and analyzed using the Statistical Package for Social Science, SPSS version 21. Ninety percent (90%) of participants were highly knowledgeable with regards to routine medical checkup as a very important practice among health professionals. Similarly, participants exhibited a positive perception towards medical checkups. 98.7% said medical checkups are important whilst 99.0% said they would encourage the practice of periodic medical checkup. Prevalence of periodic medical checkup was 91.0%. Most of the participants’ recommended that medical checkups be covered by health insurance whilst health facilities should also ensure an annual examination of its staff. There is a high prevalence of medical checkup among health care personnel at the teaching hospital under study, there is also a positive attitude as well as a high level of knowledge regarding the practice.Keywords: Medical Checkup, Examination, Knowledge, Health Workers, Perception and Practice